Pengaruh Financial Socialization, Financial Knowledge, Financial Experience terhadap Financial Management Behavior dengan Locus of Control sebagai Variabel Mediasi pada Pengguna Paylater - Dewanti, Vicky Pradita; Haryono, Nadia Asandimitra (Jurnal Ilmu Manajemen, 2021)
The research of this study investigates financial management behaviour among the user of the Paylater in Surabaya. It also analyzes the relationship between financial socialization, financial knowledge, financial experience, and locus of control as a mediating variable. This research is conclusive causality, used purposive sampling and snowball sampling techniques. The total number of respondents obtained was 234 respondents by distributing questionnaires online. Data analyzed using the Structural Equation Modeling (SEM) analysis technique in the AMOS software. The results show that financial knowledge significantly impacts financial management behaviour, while financial socialization, financial experience, and locus of control do not affect financial management behaviour. The mediation testing result shows that locus of control cannot mediate between financial knowledge and financial management behaviour. Because the sample dominant is the student and age range between 15 and 24, almost all of them still have income from their parents, so they can not manage financial independence to the greatest extent and do not have much experience related to finance. It was also caused by female respondents who often engage in impulsive buying. This study could be helpful to references for various parties, especially Paylater users, to be responsible for making financial decisions and wise in managing their finances.